Linguoculturological Field As the Unity of Language and Culture - Kadirova Barno Raimovna (Zien Journals, 2024)
The article is devoted to the study of the linguistic and cultural field, describing its structure and content. The authors consider the systemicity of language, conditioned by a set of fields as the basis of the physical picture of the world, to be the starting point in the formation of the linguoculturological field. The synthesis of linguistic and extra-linguistic knowledge is reflected in the unification of linguistic units of different levels that interpret the cultural concept - the name of the field, mainly vocabulary and phraseology of the language. Important principles for studying the linguoculturological field are the semasiological and onomasiological aspects.
Keywords: Anthropocentrism; systematicity; thesaurus